Climate variability and educational attainment: Evidence from rural Ethiopia. (November 2016) - Randell, Heather; Gray, Clark
Highlights: Examines links between climate variability and education in rural Ethiopia. Rainfall during the summer agricultural season is positively linked to education. Milder temperatures during early childhood are positively associated with schooling. Future climate change may reduce school participation in rural Sub-Saharan Africa. This could slow progress toward human development goals and poverty alleviation. Abstract: This paper examines the effects of climate variability on schooling outcomes in rural Ethiopia. Investments in education serve as an important pathway out of poverty, yet reduced agricultural productivity due to droughts or temperature shocks may affect educational attainment if children receive poorer nutrition during early childhood, are required to participate in household income generation during schooling ages, or if households can no longer pay for school-related expenses. We link longitudinal socioeconomic, demographic, and schooling data from the Ethiopian Rural Household Survey to high-resolution gridded climate data to measure exposure to temperature and precipitation relative to historical norms. We then estimate a set of multivariate regression models to understand how climate variability impacts grade attainment and school enrollment. Results indicate that early life climatic conditions – namely milder temperatures during all seasons and greater rainfall during the summer agricultural season – are associated with an increased likelihood of a child having completed any education. In addition, greater summer rainfall during both early life and school ages is associated with having completed any schooling as well as with attending school at the time of the survey. These findings suggest that future climate change may reduce children's school participation in rural Sub-Saharan Africa, slowing progress toward human development goals and poverty alleviation.